Obraz Wojska Polskiego i podziemia poakowskiego w latach 1945–1946 w świetle raportów czechosłowackiego wywiadu - Halczak, Bohdan; Šmigel, Michał (Slavia Occidentalis, 2015)
In the years 1945–1946, Czechoslovak intelligence operated in Poland. These secret intelligence reports are now a valuable resource for historians. In 1945–1946, in the mountainous regions of south-eastern Poland, near the border with Czechoslovakia, a civil war was ongoing. Government forces and the anti-communist resistance were fighting each other. The events in south-eastern Poland were carefully observed by Czechoslovak intelligence. Czechoslovak agents critically evaluated government forces. In their opinion, this formation was ill-equipped and poorly trained. The leaders were often Soviet officers who didn’t even know Polish. Many soldiers in the government army secretly sympathised with the anti-communist underground. Czechoslovak agents positively evaluated the anti-communist resistance movement. According to the reports, the underground was numerous, disciplined and well-organised. The partisans had high morale and enjoyed widespread support from the civilian population. However, the Polish Army was an official ally of Czechoslovakia.